Plant blindness profile of high school students in Hulu Gurung sub-district, Kapuas Hulu district - Tasya Putriani; Ari Sunandar; Mahwar Qurbaniah (University of Muhammadiyah Malang, 2023)
People often forget about plants as living organisms that are essential for life which characterizes plant blindness. Plant blindness can occur in students. The objectives of this study are identifying plant blindness in high school student in Hulu Gurung. This research was conducted in January 2023 in the even semester of 2022/2023. The population in this study were all students of SMPN 1 Hulu Gurung (Junior High School) and SMAN 1 Hulu Gurung (Senior High School). Sample selection using Simple Random Sampling technique. The instruments used were questionnaires and direct interviews. Methods for data analysis using qualitative descriptive methods. The results showed that students still lack knowledge about local vegetables. The percentage of students recognizing vegetables was 15% in senior high school students and 4% in junior high school students. There were 6 vegetable species that were not recognized at all, namely Solanum lasiocarpum, Ficus sp., Mangifera pajang, Polypodium sp., Ficus sp., and Smilax leucophylla. In the future local vegetables can be better recognized amidst the presence of imported vegetables. The diversity of local vegetable crops must be maintained through conservation strategies, one of which is to avoid plant blindness as early as possible.